Camphor revisited: studies of 2,5-diketocamphane 1,2-monooxygenase from Pseudomonas putida ATCC 17453. - Taylor, D G (1986)
The oxygenating component of 2,5-diketocamphane 1,2-monooxygenase from Pseudomonas putida ATCC 17453 was purified to homogeneity by a combination of ammonium sulfate fractionation and chromatography on DEAE-cellulose and polyanion SI-17 columns. It had an Mr of 78,000, bound one molecule of nonautooxidizable flavin mononucleotide (FMN), consisted of two subunits of equal molecular weight, and existed in two electrophoretically distinguishable active forms. The oxygenating complex was constructed from equimolecular amounts of an NADH oxidase, which could be purified separately (Mr, 36,000), and the oxygenating component. Most of the NADH oxidase dissociated from the oxygenating component during purification, although traces remained, to give the final preparation of the oxygenating component significant oxygenase activity. FMN did not dissociate significantly from the oxygenating component during purification, but it was not covalently bound and could be removed under a variety of conditions. Binding between the two proteins that made up the active complex was fairly weak and freely reversible. It probably occurred through the FMN which was strongly bound to the oxygenating component and for which the NADH had a weak binding site. Iron was not present at a significant level in the oxygenating component, and in common with other characterized Baeyer Villiger monooxygenases, 2,5-diketocamphane 1,2-monooxygenase was found to be a simple flavoprotein.